Establishment of induced pluripotent stem cell lines derived from Parkinson’s disease Mexican patients: A sporadic (UNAMi002-A) and a familial (UNAMi003-A) case carrying a mutation in PINK1 - Flores-Ponce, Xóchitl; López-Ornelas, Adolfo; Escobedo-Avila, Itzel; Rodríguez-Violante, Mayela; Dávila-Ortiz de Montellano, David; Cervantes-Arriaga, Amín; Monroy-Jaramillo, Nancy; Campos-Romo, Aurelio; Velasco, Iván (Stem cell research, 2024)
Parkinson’s disease (PD) is characterized by the progressive loss of dopaminergic neurons in the substantia nigra pars compacta, which results in a prominent reduction of striatal dopamine levels leading to motor alterations. The mechanisms underlying neurodegeneration in PD remain unknown. Here, we generated an induced pluripotent stem cell line from dermal fibroblasts of a Mexican patient diagnosed with sporadic PD (UNAMi002-A) and another cell line from dermal fibroblasts of a patient carrying the point mutation c.1423delC in PINK1 (UNAMi003-A). These patient-derived iPS cell lines offer the possibility of modeling PD and understanding the mechanisms that contribute to dopamine neuron loss.